2021
DOI: 10.1063/5.0052649
|View full text |Cite
|
Sign up to set email alerts
|

Improving Seebeck coefficient of thermoelectrochemical cells by controlling ligand complexation at metal redox centers

Abstract: Practical conversion of waste heat into electricity via thermoelectrochemical cells requires high Seebeck coefficient (α) to increase cycle efficiency. The complexation of Cu2+ species with dissolved multidentate ligands, such as ethylenediaminetetraacetic acid, and the control of dimerization equilibria with bridging ligands, such as 1,6-diaminohexane or 1,2-diaminoethane, dramatically improve, by up to ∼185%, the magnitude of the α of Cu/Cu2+ thermoelectrochemical cells. This results in the highest α for any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…So far, the use of the quantum-chemical method to explain the Se of TEC is still limited. Recently, Gunawan et al 49 applied this method to the Cu/Cu 2+ system with flexible ligands and showed that the Se values calculated under assumed ligand conformations were on the same order as the measured values.…”
Section: Introductionmentioning
confidence: 87%
“…So far, the use of the quantum-chemical method to explain the Se of TEC is still limited. Recently, Gunawan et al 49 applied this method to the Cu/Cu 2+ system with flexible ligands and showed that the Se values calculated under assumed ligand conformations were on the same order as the measured values.…”
Section: Introductionmentioning
confidence: 87%
“…There are various methods for improving the Seebeck coefficient of materials. Techniques such as hydrazine treatment [ 22 ], ionic liquid post-processing [ 23 ], alloying [ 24 ], control of material alignment [ 25 ], and energy filtering through nanoparticle deposition [ 26 ] can be employed to enhance the Seebeck coefficient. However, in this work, we focused on creating sensors using commonly available materials from the market without additional processing steps.…”
Section: Methodsmentioning
confidence: 99%
“…The energy generation mechanism can be based on both phase and chemical transformations of electrolytes [ 17 ] and redox processes in the electrolyte, while the electrodes are inert [ 18 , 19 , 20 ]. Another type of thermocells are systems with reversible electrodes [ 2 , 21 , 22 ]. These systems require a regular change of the thermal gradient direction; however, they show a rather high efficiency level and a hypothetical Seebeck coefficient for systems with aqueous electrolytes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%